Faktor-Faktor yang Mempengaruhi Pertumbuhan Area Pinggiran (Studi Kasus: di Kecamatan Karanganyar Sebagai Ibukota Kabupaten Karanganyar) - Baiquni, M. Irsyad; Setioko, Bambang (Magister Pembangunan Wilayah dan Kota,Undip, 2014)
Urban population growth, has resulted in an increased need for land as well. Due to limited land in urban areas, the development will be expanded in the fringe area. Karanganyar sub district as the district capital of Karanganyar district is the center of government and serves as urban, has a fairly extensive undeveloped land. But the phenomenon occurred housing development and new settlements, in the fringe area. So need to know what the cause of the growth. One way is by looking for any factors that affect the growth of fringe areas in the Karanganyar sub district as the capital of district. This study uses a quantitative deductive method. Sampling using random sampling techniques, taken from stakeholders of the growth of fringe areas in the Karanganyar sub district. The analysis was done by descriptive analysis to describe urban areas and fringe areas, and quantitative analysis through factor analysis. The results showed there were five (5) factors affecting the growth of fringe area in the Karanganyar sub district as the capital of district, namely an availability of social facilities, an service, an economic and environmental, an ease, and a comfort factors.